Reconstruction of Absolute Competence of Religious Courts in Criminal Cases of Domestic Violence in Indonesia - Izzuddin, Ahmad; Alfikri, Ahmad Faiz Shobir (Hukum Keluarga Islam IAIN LANGSA, 2025)
The authority of the religious courts in Indonesia in cases of domestic violence is limited to the civil sphere as grounds for divorce. Conversely, the District Court is responsible for resolving cases with criminal elements. This legal fragmentation prevents victims from obtaining comprehensive justice due to the lengthy and complex legal process. This research highlights the legal gap by analyzing the need for reconstruction of the absolute authority of the religious court to handle the criminal aspects of domestic violence cases. This research is a normative legal statutory and conceptual approach. Analysis of legal materials is done by qualitative methods. The results of this research are legal reconstruction offered in the form of expansion of the absolute competence of the religious court in handling the criminal aspects of domestic violence with the authority to provide protection orders to victims during the judicial process and impose criminal sanctions on perpetrators of domestic violence. The success of this reconstruction, based on the analysis of Soerjono Soekanto's theory of legal effectiveness, depends on harmonizing regulations, increasing law enforcement's competence, providing adequate facilities, increasing public legal literacy, and cultural transformation that supports justice and equality. This legal reconstruction contributes to the efficient resolution of domestic violence cases in line with the principles of judicial power, namely the achievement of simple, fast, and low-cost justice.